Administrative and Legal Regulation of the Development and Use of Artificial Intelligence - G. G. Lyannoy (Сибирское юридическое обозрение, 2024)
The paper examines the difference between the terms “digital economy” and “digitalization of the economy”. Having conducted research, the Author comes to the conclusion that the term “digital economy” cannot be used to denote technologies being used in global economies. Digitalization of the economy is currently underway all over the world. The era of digital economy has not come yet because mankind has not seen a new technological leap as a part of evolution to result in creating artificial intelligence. The introduction of artificial intelligence technology into the economy, which will have been digitalized by then, will lead to a single digital economy in the meaning the term “digital economy” implies. The Author thinks that without integration of these two phenomena, the use of the term “digital economy” is erroneous. Having studied the historical prerequisites for the emergence of the phenomenon of “digitalization of the economy”, the Author comes to the conclusion that the only country in the world that was on the verge of building a state based on digitalization technologies was the USSR. That took place 40 years before the term “digital economy” appeared. The paper goes on to say about the legal regulation of creating artificial intelligence  in countries such as the United States of America, England, Germany, France, Italy, Poland, Israel, India, China, South Korea and the Russian Federation. The paper draws the examples of legislation of various countries that regulate the legal status of artificial intelligence, as well as their various approaches to the development of artificial intelligence. Moreover, the study highlights the problems of a non-legal nature that lawyers and users will face when they use artificial intelligence technology. Artificial intelligence is viewed in the context of business security. The Author is certain that administrative and legal institutions have to regulate this area of activity.